Clinical issues in anatomy / Frederic Martini, Kathleen Welch - Martini, FredericAuthor
This new student supplement includes discussions on diseases, dysfunctions, and injuries that are referenced throughout HUMAN ANATOMY, 5TH EDITION. Icons throughout the text alert the user to topics that Clinical Issues in Anatomy covers and illustrates in great depth.